2018
DOI: 10.3389/feart.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Water Quantification and Incorporation in Transition Zone Minerals: Wadsleyite, Ringwoodite and Phase D Using ERDA (Elastic Recoil Detection Analysis)

Abstract: Hydrous wadsleyite, ringwoodite, and phase D have been synthesized in the MgO-SiO 2-H 2 O and MgO-FeO-SiO 2-H 2 O systems at mantle transition zone conditions (15-21 GPa and 1,100-1,700 • C) to investigate their water incorporation using Elastic Recoil Detection Analysis (ERDA), which is an absolute quantitative method. Wadsleyite and ringwoodite water contents vary from 0.1 to 3.2 wt% H 2 O and for ringwoodite containing up to 1.16 wt% H 2 O we observe that the (Mg+Fe)/Si ratio vs. water content follows the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 57 publications
3
40
2
Order By: Relevance
“…The C H2O in Fe‐bearing wadsleyite measured in this study is higher than the values reported by Bolfan‐Casanova et al. (2018). Note that the H 2 O content in the starting material in Bolfan‐Casanova et al.…”
Section: Results and Comparison With Previous Studiescontrasting
confidence: 79%
See 3 more Smart Citations
“…The C H2O in Fe‐bearing wadsleyite measured in this study is higher than the values reported by Bolfan‐Casanova et al. (2018). Note that the H 2 O content in the starting material in Bolfan‐Casanova et al.…”
Section: Results and Comparison With Previous Studiescontrasting
confidence: 79%
“…Note that the Paterson (1982) calibration was used in Sun et al (2018), which may underestimate C H2O . By adjusting their results to a newer calibration using a correction factor of 100/55 given by Bolfan-Casanova et al (2018), the C H2O in Sun et al (2018) becomes 1.7 ∼ 1.8 wt.%, which is slightly higher than in this study (∼1.4 wt.% at 1720 K) (Figure 3). However, this difference could be caused by experimental uncertainties, including the uncertainty of the correction factor between different infrared calibrations, experimental temperature, and FTIR spectra baseline subtraction.…”
Section: H2o /Solubility In Fe-bearing Wadsleyitementioning
confidence: 51%
See 2 more Smart Citations
“…To ensure the compiled water storage capacity measurements are internally consistent, we have corrected all the FTIR measurements for olivine to the Withers et al (2012) calibration. Though no independent infrared absorption calibration has been established specifically for OH in either wadsleyite or ringwoodite, it has been shown that the Paterson (1982) calibration underestimates water concentrations in wadsleyite and ringwoodite by ∼55% relative to the ERDA technique (Bolfan-Casanova et al, 2018). Here, we corrected those water concentrations in wadsleyite and ringwoodite determined by FTIR based on the Paterson (1982) calibration by this amount.…”
Section: Appendix B: Selection and Correction Of Experimental Data Onmentioning
confidence: 99%